A Review of Strategies to Prevent On-Site Construction Waste - Hassan, Mohamed Hussein; Mohamed, Abdifitah Yusuf; Ibrahim, Ahmed Mohamud; Roble, Zakariye Abdullahi; Balasbaneh, Ali Tighnavard (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
One of the most important concerns that improves building profitability is the implementation of a positive approach to minimize construction waste. This paper will discuss the roots of construction waste, current waste reduction strategies, and lastly the possible use of waste management. Furthermore, the key environmental priority for this issue should be to control and mitigate construction waste generation. The purpose of this study is to provide prevention measures, and the rising tide of public awareness is all conspiring to modify the face of waste management. Clients, contractors, suppliers, and designers Architects & Engineers all have opportunities and duties to reduce construction waste. The outcomes of this study will assist academics in furthering their research into important management strategies for reducing on-site building waste.